The Effect of Mathematics Anxiety on the Problem-Solving Ability - Rahmani, Irma (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2024)
Math anxiety is a disturbing condition in mathematics learning. The influence of math anxiety is one of the causes of low student problem-solving ability. This study aims to obtain the influence of mathematics anxiety on the problem-solving ability of grade XI science students of SMA Negeri 1 Gerung for the 2023/2024 school year. The type of research used in this study is quantitative research with ex-post facto research methods. The data analysis used is inferential statistical analysis. The results of the t-test that obtained a value of t_hitung = 6.955 > t_tabel = 1.967 with a sig value = 0.05 or 5% then there is a significant influence between mathematical anxiety on problem solving ability. The results of the regression equation Y ̂ = 4.072 – 0.831X, showed that there was a negative relationship between mathematical anxiety and problem-solving ability. The result of a correlation coefficient of 0.459 shows that between mathematical anxiety and problem-solving ability has a moderate relationship. The coefficient of determination points to 0.617 or 61.7%.